3-DOF Inertial Piezoelectric Actuator for Angular Positioning of the Optical Mirror - Andrius Ceponis; Dalius Mazeika; Regimantas Bareikis (IEEE Access)
Article introduces a novel 3-DOF piezoelectric actuator designed to achieve the high-precision angular motion of a spherical rotor and an optical mirror around three axes. The actuator consists of three interlinked piezoelectric bimorph plates arranged in a low-profile triangular structure. Each piezoelectric plate contains a cylindrical contact that is used to transfer the vibrations to induce the angular motion of the rotor. The actuator has a low profile and is mounted on a printed circuit board (PCB), enhancing its structural integrity. The actuator occupies a footprint of 986 mm2 and, including the rotor, weighs 35.5 g. The actuator operation is based on the inertial stick-slip principle, using the first and second out-of-plane bending modes of the bimorph plates. Simultaneous excitation of the second vibration mode of all three bimorph plates produces angular motion of the rotor around the vertical axis. In contrast, the excitation of the first vibration mode of the individual plate enables angular motion around one of the horizontal axes. Numerical analysis identified the vibration modes, resonant frequencies, and mechanical and electromechanical characteristics of the actuator, leading to design optimization of clamping beams and contact locations on the bimorph plates. Experimental measurements revealed that the maximum rotation speeds are 363.7 RPM around the vertical axis and 129.1 RPM around the horizontal axis. Maximum torques of 218.2 mN/m and 159.7 mN/m were achieved around the vertical and horizontal axes, respectively, when the actuator is driven at 200 V $_{p-p}$ . The actuator demonstrated angular resolutions of 2.47 mrad and 1.033 mrad for the vertical and horizontal axes, respectively.